2014
DOI: 10.4081/reumatismo.2014.767
|View full text |Cite
|
Sign up to set email alerts
|

Pain in fibromyalgia and related conditions

Abstract: Pain is the hallmark symptom of fibromyalgia (FM) and other related syndromes, but quite different from that of other rheumatic diseases, which depends on the degree of damage or inflammation in peripheral tissues. Sufferers are often defined as patients with chronic pain without an underlying mechanistic cause, and these syndromes and their symptoms are most appropriately described as "central pain", "neuropathic pain", "nonnociceptive pain" or "central sensitivity syndromes". The pain is particular, regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 66 publications
(88 reference statements)
1
26
0
6
Order By: Relevance
“…Those with broader pain distributions demonstrated significantly poorer scores on the other elements of the SPACE symptom cluster (Lai et al, 2017). Similar findings have been reported in the context of TMD (Slade et al, 2013) and FM (Cassisi et al, 2014). …”
Section: Chronic Overlapping Pain Conditions (Copcs): the Diagnossupporting
confidence: 89%
“…Those with broader pain distributions demonstrated significantly poorer scores on the other elements of the SPACE symptom cluster (Lai et al, 2017). Similar findings have been reported in the context of TMD (Slade et al, 2013) and FM (Cassisi et al, 2014). …”
Section: Chronic Overlapping Pain Conditions (Copcs): the Diagnossupporting
confidence: 89%
“…The complex features of the syndrome and its various symptoms are partially explained by central sensitization processes that interact with psychological and social factors, leading to a phenomenon where the impact of each component is multiplied and acts in a synergic manner [4, 5]. Given its multifaceted nature and the poor efficacy of standard medical interventions, the integration of different health disciplines for its understanding and for the development of specific treatments has long been advocated [610].…”
Section: Introductionmentioning
confidence: 99%
“…Cassisi et al emphasized the association between FMS, and central nervous system anomalies, MPS, BJHS, and temporomandibular joint disorders, and indicated the necessity of a multidisciplinary approach so as to relieve symptoms of pain, and restricted mobility suffered by these patients [26]. Fitzcharles et al reported that FMS patients with low socioeconomic status experienced worse functional disability, and more severe symptoms compared with other FSM patients despite the same levels of pain, anxiety, and depression due to the differences in the perception of the disease state [27].…”
Section: Discussionmentioning
confidence: 99%